Social activism in Southeast Asia - Ford, Michele (Routledge contemporary Southeast Asia series, 2013)
"Brings together cutting-edge accounts of social movements concerned with civil and political rights, globalization, peace, the environment, migrant and factory labour, the rights of middle- and working-class women, and sexual identity in an overarching framework of analysis that forefronts the importance of human rights and the state as a focus for social activism in a region characterized by a history of authoritarian developmentalism and weak civil society"--Provided by publisher.